Osmotic stress upregulates the transcription of thiamine (vitamin B1) biosynthesis genes (THIC and THI4) in oil palm (Elaies guineensis) - Wong, Sook Yee; Abdul Aziz, Syamimi Diyana; Balia Yusof, Zetty Norhana (Academic Journals, 2016)
Thiamine or vitamin B1 comprises a pyrimidine moiety and a thiazole moiety. Thiamine pyrophosphate (TPP), the active form of thiamine, acts as a cofactor for various major enzymes, for example, transketolase (TK), α-ketoglutarate dehydrogenase (KGDH) and pyruvate dehydrogenase (PDH). It is suggested that TPP plays another important role, which is protecting plants against abiotic and biotic stresses such as osmotic stress. In this study, the gene transcripts of first two enzymes in thiamine biosynthesis pathway, THIC and THI1/THI4 were identified and amplified from oil palm tissues. Primers were designed based on sequence comparison of the genes from Arabidopsis thaliana, Zea mays, Oryza sativa and Alnus glutinosa. Oil palm’s responses in terms of the expression profiles of these two thiamine biosynthesis genes to an osmotic stress inducer, polyethylene glycol (PEG) were examined. The level of gene transcripts was analyzed using reverse transcriptase polymerase chain reaction (RT-PCR) and both THIC and THI1/THI4 gene transcripts were successfully amplified. The levels of transcription were measured and the results showed that the expression of THIC gene transcripts showed an increase of up to 200% in 1% PEG treated plant as compared to non-treated plant while the expression of THI1/THI4 gene transcripts showed an increase of up to 100% in treated plant as compared to non-treated plant. However, increase in concentration of PEG showed decrease in amount of transcription level for both gene transcripts. The results support the suggestion that thiamine may play an important function in plant defense against stresses as these findings may lead to an overexpression of thiamine in general.